The COVID-19 pandemic and follow-up for shoulder surgery: The impact of a shift toward telemedicine on validated patient-reported outcomes. (July 2023) - Sabbagh, Ramsey; Shah, Nihar; Jenkins, Sarah; Macdonald, Jacob; Foote, Austin; Matar, Robert; Steffensmeier, Andrew; Grawe, Brian
Introduction: The emergence of COVID-19 and its ensuing restrictions on in-person healthcare has resulted in a sudden shift towards the utilization of telemedicine. The purpose of this study is to assess patient satisfaction and patient-reported outcome measures (PROMs) for individuals who underwent follow-up for shoulder surgery using telemedicine compared to those who received traditional in-person clinic follow-up. Methods: Patients who underwent either rotator cuff repair or total shoulder arthroplasty during a designated pre-COVID-19 (traditional clinic follow-up) or peri-COVID-19 (telemedicine follow-up) span of time were identified. PROMs including the American Shoulder and Elbow Surgeons standardized assessment form, the three-level version of the EQ-5D form, the 12-Item Short Form survey, and a modified version of a published telemedicine survey were administered to participants six months post-operatively via phone call. Results: Sixty patients agreed to participate. There was no significant difference between the pre-COVID-19 and peri-COVID-19 groups in patient satisfaction with their follow-up visit ( p = 0.289), nor was there a significant difference in PROMs between the two groups. In total, 83.33% of the telemedicine group and 70.37% of the in-person clinic group preferred traditional in-person follow-up over telemedicine. Discussion: In a cohort of patients who underwent telemedicine follow-up for shoulder surgery during the COVID-19 pandemic, there was no difference in patient satisfaction and PROMs compared to traditional in-person clinic follow-up. This study indicates that while the majority of participants preferred face-to-face visits, patients were relatively satisfied with their care and had similar functional outcome scores in both groups, despite the large disruption in healthcare logistics caused by COVID-19.